The long non-coding RNA HOTTIP promotes progression and gemcitabine resistance by regulating HOXA13 in pancreatic cancer - Li, Zhihua (J Transl Med, 2015)
BACKGROUND: The human genome encodes many long non-coding RNAs (lncRNAs). However, their biological functions, molecular mechanisms, and the prognostic value associated with pancreatic ductal adenocarcinoma (PDAC) remain to be elucidated. Here, we identify a fundamental role for the lncRNA HOXA transcript at the distal tip (HOTTIP) in the progression and chemoresistance of PDAC. METHODS: High-throughput microarrays were performed to detect the expression profiles of lncRNAs and messenger RNAs in eight human PDAC tissues and four pancreatic tissues. Quantitative real-time PCR was used to determine the levels of HOTTIP and HOXA13 transcripts in PDAC cell lines and 90 PDAC samples from patients. HPDE6 cells (immortalized human pancreatic ductal epithelial cells) and corresponding adjacent non-neoplastic tissues were used as controls, respectively. The functions of HOTTIP and HOXA13 in cell proliferation, invasion, and epithelial-mesenchymal transition were evaluated by targeted knockdown in vitro. CCK-8 assays, colony formation assays, and xenografts in nude mice were used to investigate whether targeted silencing of HOTTIP could sensitize pancreatic cancer cells to gemcitabine. Immunohistochemistry was performed to investigate the relationship between HOXA13 expression and patient outcome. RESULTS: Microarray analyses revealed that HOTTIP was one of the most significantly upregulated lncRNAs in PDAC tissues compared with pancreatic tissues. Quantitative PCR further verified that HOTTIP levels were increased in PDAC cell lines and patient samples compared with controls. Functionally, HOTTIP silencing resulted in proliferation arrest by altering cell-cycle progression, and impaired cell invasion by inhibiting epithelial-mesenchymal transition in pancreatic cancer. Additionally, inhibition of HOTTIP potentiated the antitumor effects of gemcitabine in vitro and in vivo. Furthermore, knockdown of HOXA13 by RNA interference (siHOXA13) revealed that HOTTIP promoted PDAC cell proliferation, invasion, and chemoresistance, at least partly through regulating HOXA13. Immunohistochemistry results revealed that higher HOXA13 expression was correlated with lymph node metastasis, poor histological differentiation, and decreased overall survival in PDAC patients. CONCLUSIONS: As a crucial tumor promoter, HOTTIP promotes cell proliferation, invasion, and chemoresistance by modulating HOXA13. Therefore, the HOTTIP/HOXA13 axis is a potential therapeutic target and molecular biomarker for PDAC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-015-0442-z) contains supplementary material, which is available to authorized users.